(untitled) (Збірник наукових праць Галузеве машинобудування будівництво, 2018)
The article considers works execution organization at reconstruction and renovation of residential and public buildings for embedded systems with usage of slabs lifting method at restrained urban conditions. The paper suggests usage features of the slabs lifting method at building reconstruction conditions. The technology of reconstruction with the usage of slabs lifting method allows to refuse practically the use of lifting cranes and to reduce significantly (up to 50%) the required building area compared with the lifting crane construction methods of embedded structures. It allows to perform the reconstruction without restriction of traffic on adjoining streets and to perform construction in restrained urban conditions.